Bevacizumab and Combination Chemotherapy in rectal cancer Until Surgery (BACCHUS): a phase II, multicentre, open-label, randomised study of neoadjuvant chemotherapy alone in patients with high-risk cancer of the rectum. Issue 1 (December 2015) - Glynne-Jones, R.; Hava, N.; Goh, V.; Bosompem, S.; Bridgewater, J.; Chau, I.; Gaya, A.; Wasan, H.; Moran, B.; Melcher, L.; MacDonald, A.; Osborne, M.; et al.
Abstract Background In locally advanced rectal cancer (LARC) preoperative chemoradiation (CRT) is the standard of care, but the risk of local recurrence is low with good quality total mesorectal excision (TME), although many still develop metastatic disease. Current challenges in treating rectal cancer include the development of effective organ-preserving approaches and the prevention of subsequent metastatic disease. Neoadjuvant systemic chemotherapy (NACT) alone may reduce local and systemic recurrences, and may be more effective than postoperative treatments which often have poor compliance. Investigation of intensified NACT is warranted to improve outcomes for patients with LARC. The objective is to evaluate feasibility and efficacy of a four-drug regimen containing bevacizumab prior to surgical resection. Methods/design This is a multi-centre, randomized phase II trial. Eligible patients must have histologically confirmed LARC with distal part of the tumour 4–12 cm from anal verge, no metastases, and poor prognostic features on pelvic MRI. Sixty patients will be randomly assigned in a 1:1 ratio to receive folinic acid + flurourcil + oxaliplatin (FOLFOX) + bevacizumab (BVZ) or FOLFOX + irinotecan (FOLFOXIRI) + BVZ, given in 2 weekly cycles for up to 6 cycles prior to TME. Patients stop treatment if they fail to respond after 3 cycles (defined as ≥ 30 % decrease in Standardised Uptake Value (SUV) compared to baseline PET/CT). The primary endpoint is pathological complete response rate. Secondary endpoints include objective response rate, MRI tumour regression grade, involved circumferential resection margin rate, T and N stage downstaging, progression-free survival, disease-free survival, overall survival, local control, 1-year colostomy rate, acute toxicity, compliance to chemotherapy. Discussion In LARC, a neoadjuvant chemotherapy regimen - if feasible, effective and tolerable would be suitable for testing as the novel arm against the current standards of short course preoperative radiotherapy (SCPRT) and/or fluorouracil (5FU)-based CRT in a future randomised phase III trial. Trial registration Clinical trial identifier BACCHUS:NCT01650428